Can Sea Urchin Eggs Shelf-Life Be Extended by Cold Storage? - Campos, Sara; Paredes, Estefanía; Troncoso, Jesús (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(1): 068–071